Ciguatera fish poisoning in France: experience of the French Poison Control Centre Network from 2012 to 2019. (4th March 2021) - de Haro, Luc; Schmitt, Corinne; Sinno-Tellier, Sandra; Paret, Nathalie; Boels, David; Le Roux, Gaël; Langrand, Jérôme; Delcourt, Nicolas; Labadie, Magali; Simon, Nicolas
Abstract: Introduction: Ciguatera fish poisoning (CFP) is a common Poisoning in the tropical countries. France is directly concerned with French tourists in endemic area and with French citizens living in the French overseas territories. Method: Retrospective, descriptive study of CFP cases handled by the French Poison Control Centre Network from 2012 through 2019. Results: Fifty-two events were studied concerning 130 patients. The fish species was identified for 41 events, mainly belonging to five fish families: 14 groupers, 11 snappers, 5 jacks, 4 parrotfishes, 4 barracudas. The origin of the fish was the Atlantic Ocean (23 events), the Indian Ocean (17 events) and the Pacific Ocean (12 events). 91% of the poisonings occurring in the Atlantic Ocean began with gastrointestinal effects while in 44% of events occurring in the Pacific Ocean, the patients had no gastrointestinal effects (onset with neurological symptoms: paraesthesia and dysesthesia). The evolution of the 130 patients has been classic for CFP with persistent symptoms during 1 to 45 weeks. Numerous patients reported exacerbation of neurological signs several months after poisoning following consumption of alcoholic beverages (23 patients) or seafood (19 patients). Discussion: Medical practitioners in Europe must be trained to manage CFP as cases are reported with tourists returning from endemic areas but also with poisoned patients far from tropical areas after consumption of imported fish.